DETERMINANTS OF RURAL HOUSEHOLD SAVINGS BEHAVIOR: THE CASE OF AMBO DISTRICT, OROMIA NATIONAL REGIONAL STATE, ETHIOPIA - Kumala DEKSISA; Mulubrihan BAYISSA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The study was conducted to identify factors affecting household saving behavior of rural households in the district of Ambo district. Data for the study was collected from 370 households from two Kebeles. Both primary and secondary sources were used for this study and multi-stage sampling technique was used to contact with the study units (households). To attain the objectives of the study the researcher used both descriptive and econometric analysis. With descriptive analysis percentages, figures, graphs, charts and tables were used to present determinants of private saving. The results ultimately reveals that the Sex of the head of the household, Family size, land size, Access to credit and annual income are significantly influencing the saving behavior in the entire study area. Based on these findings, we recommend that government policy intervention should focus on increasing the availability and accessibility of financial institutions, awareness creation and education on the importance saving and saving modalities, planning and expenditure controlling habit, socio-cultural saving barriers, increasing interest rate, and inflation and unemployment combating strategies to augment saving capacity, investment and then economic growth.